“Василіанське бароко” - Ісіченко, І. (Слово і Час, 2011)
У статті автор аналізує внесок монахів-василіан у літературне життя України доби бароко. Розглянуто творчість архієпископів Йосафата Кунцевича та Лева Кревзи, єпископа Якова Суші. Окрему увагу приділено діяльності Почаївського монастиря з його друкарнею, що став головним видавничим і культуротворчим осередком XVIII ст. Відзначається чільне місце серед почаївських видань “Народовіщанія” та “Богогласника”. Автор використовує термін “василіанське бароко” й намагається окреслити його параметри. The paper summarizes the contribution of Basilian monks to the literary life in Ukraine of the Baroque era. The author concentrates on the works of archbishops Josaphat Kuncewicz and Leon Kreuza as well as on those of bishop Jakob Susza. Much attention is given to Pochaiv monastery with its printing works which became the centre of publishing and cultural activities in the 18th century Ukraine. The pivotal point of publishing activities in Pochaiv is considered to be marked with two editions, namely “Narodovishchaniye” (a collection of sermons) and “Bohohlasnyk” (a collection of Ukrainian religious songs). In order to describe this state of matters, the author introduces the term “Basilian Baroque” and outlines its principal parameters. В статье анализируется вклад монахов-базилиан в литературную жизнь Украины эпохи барокко. Рассматривается творчество архиепископов Иосафата Кунцевича и Льва Кревзы, епископа Иакова Суши. Особенное внимание обращается на деятельность Почаевского монастыря с его типографией, ставшего главным издательским и культурным центром XVIII в. Отмечается ведущее место среди почаевских изданий “Народовеща ния” и “Богогласника”. Автор использует термин “базилианское барокко” и стремится описать его параметры.